Tasawuf dan Tantangan Modernitas - Tri Astutik Haryati; Mohammad Kosim (Ulumuna, 2010)
Sufism is one of the branch of Islamic disciplines that grows significantly and becomes an inseperable subject of Islamic scholarship. Sufism is personal spiritual experience that emphasises more on feeling than logic. Therefore it is often named as a knowledge of taste (dwauq). Such emphasize on inner dimension of human faculties often creates tension between sufism and modern life which venerates materials, competition, intrigue, deception, greedy, and attachment of worldly life. The tension occurs mainly because sufism do stress on humble and modest life, escape from worldly life, all of which are relevant to traditional society rather than rational and modern ones. However, in contrast to such widely presumed tension, sufism remains urgent for modern life because it becomes spiritual injection for human matters related to modern life and helps resolve problems of materialistically secular, individual and hedonistic life.